2020
DOI: 10.1101/2020.04.01.019422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schwann cell plasticity regulates neuroblastic tumor cell differentiation via epidermal growth factor-like protein 8

Abstract: The remarkable plasticity of Schwann cells (SCs) enables the acquisition of repair-specific functions essential for peripheral nerve regeneration. We hypothesized that this plastic potential is manifested in stromal SCs found within mostly benign-behaving peripheral neuroblastic tumors. To shed light on the cellular state and impact of stromal SCs, we performed transcriptome profiling of human ganglioneuromas and neuroblastomas, rich and poor in SC-stroma, respectively, as well as human injured nerves, rich in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The biological function of EGFL8, encoding 'EGF Like Domain Multiple 8', remains largely unexplored. A recent study (Weiss et al, 2021) found EGFL8 to act as neuritogen and to rewire cellular signaling by activating kinases involved in neurogenesis. Notably, EGFL7, a close paralogue of EGFL8, which is likewise expressed in brain vessels, has been implicated in various vascular functions including angiogenesis and elastogenesis (Parker et al, 2004;Lelievre et al, 2008;Nichol and Stuhlmann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of EGFL8, encoding 'EGF Like Domain Multiple 8', remains largely unexplored. A recent study (Weiss et al, 2021) found EGFL8 to act as neuritogen and to rewire cellular signaling by activating kinases involved in neurogenesis. Notably, EGFL7, a close paralogue of EGFL8, which is likewise expressed in brain vessels, has been implicated in various vascular functions including angiogenesis and elastogenesis (Parker et al, 2004;Lelievre et al, 2008;Nichol and Stuhlmann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that neuroblastomas expressing NKT1 may recruit Schwann cells to the TME through secretion of neural growth factor and in turn, the migrated Schwann cells will promote differentiation of the tumor [ 48 ]. Weiss et al further show that the Schwann cells in the neuroblastoma TME promoted tumor cell apoptosis, inhibited proliferation, and supported neurite outgrowth (a marker of neuroblastoma differentiation) via epidermal growth factor-like protein 8 [ 49 ]. The interaction between neuroblastoma and Schwann cells is not always pro-differentiation, as neuroblastoma may secrete HGMB1 into the TME to induce autophagy of the Schwann cells and ultimately promote tumor proliferation [ 50 ].…”
Section: The Therapeutic Barriers Of the Neuroblastoma Tumormentioning
confidence: 99%
“…This suggests different origins for NBs that develop within the sympathetic chain and adrenal medulla, further supported by differences in dissemination and migratory behaviour, illustrated by the migratory behaviour of NB cells transplanted onto the avian embryo NC, which migrate to form primary tumours in sympathetic ganglia, then exhibit secondary migration along nerves and blood vessels, reminiscent of Schwann progenitor migratory behaviour[ 9 , 78 , 79 , 81 ]. Malignant Sox10 expressing Schwann cell progenitor subpopulations with stem cell-like features have also been reported in human NBs, connecting adrenergic and mesenchymal compartments through transitions, reminiscent of Schwann cell progenitors[ 82 ], and may or may not be involved in the formation of the Schwannian stroma that characterises favourable NBs and benign ganglioneuromas[ 83 , 84 ]. Therefore, NBs originate from either NCSCs, SA or Schwann cell progenitors or from NC cells converted into CNS SCs by aberrant N-Myc expression with full transformation within target tissues (Figure 3 ).…”
Section: Neuroblastomamentioning
confidence: 99%